Is the Polder Model Good for the Economy?: A New Interpretation of Dutch Economic and Social History - Davids, Karel; Hart, Marjolein 't (BMGN - Low Countries Historical Review, 2014)
The book Nederland en het poldermodel [The Netherlands and the Polder Model] is a commendable effort to present a new, theory-informed interpretation of the economic and social history of the Netherlands of the last thousand years. However, this review questions the supposed causal relationship between civil society (‘polder model’) and economic growth. The authors assume that economic growth emanates from a vibrant civil society and that likewise economic decline coincides with a weakening of civil society. Upon closer inspection however, their concepts seem to be imperfectly related to the theories they claim to use as inspiration. Thesupposed waning of civil society after 1670 and after 1815 is not substantiated by historical facts either. Their thesis would have benefited greatly from a comparative analysis, both spatially and in time. The rather haphazard use of the term ‘civil society’ precludes convincing conclusions over time, while an international perspective is lacking altogether – a sadly missed opportunity. This review is part of the discussion forum 'Nederland en het poldermodel' (Maarten Prak and Jan Luiten van Zanden).Is het poldermodel goed voor de economie? Een nieuwe interpretatie van de Nederlandse economische en sociale geschiedenisHet boek Nederland en het poldermodel is een lovenswaardige poging om een nieuwe, op theoretische basis geschoeide interpretatie van de sociale en economische geschiedenis van Nederland van de laatste duizend jaar te presenteren. Deze bijdrage stelt echter vragen bij het veronderstelde causale verband tussen ‘civil society’ (het poldermodel) en economische groei. De auteurs nemen aan dat economische groei optreedt als een civil society sterk is en dat omgekeerd economisch verval zich voordoet als een civil society verzwakt. Bij nader inzien blijken hun concepten niet goed te sporen met de theorieën die hen tot inspiratie dienen. De veronderstelde kwijnende civil society na 1670 en na 1815 is ook niet op historische feiten gebaseerd. Hun stelling zou aan kracht hebben gewonnen indien zij een vergelijkende analyse hadden toegepast, zowel ruimtelijk als in de tijd. Het nogal arbitraire gebruik van de term civil society maakt het moeilijk overtuigende conclusies in de loop van de tijd te trekken, terwijl een internationaal perspectief geheel ontbreekt: een gemiste kans. Deze recensie maakt deel uit van het discussiedossier 'Nederland en het poldermodel' (Maarten Prak and Jan Luiten van Zanden).